Circumstellar interaction in Type IIn supernovae. Issue Volume 9:Issue S296(2013) (29th January 2014) - Chandra, Poonam; Chevalier, Roger A.; Chugai, Nikolai; Soderberg, Alicia M.; Fransson, Claes
Abstract: Type IIn supernovae have bright optical emission and high bolometric luminosities. Due to their high mass loss, their are expected to have dense circumstellar interaction, thus produce bright radio and X-ray emission. We aim to carry out systematic study to understand their circumstellar interaction, mass loss properties. Here, I provide specific examples of two Type IIn supernovae, 2006jd and 2010jl.